All-inkjet printed organic transistors: Dielectric surface passivation techniques for improved operational stability and lifetime. Issue 8 (July 2015) - Gomes, H.L.; Medeiros, M.C.R.; Villani, F.; Canudo, J.; Loffredo, F.; Miscioscia, R.; Martinez-Domingo, C.; Ramon, E.; Sowade, E.; Mitra, K.Y.; Baumann, R.R.; McCulloch, I.; et al.
Graphical abstract: The transistor operational stability is improved by coating the dielectric surface with a printed pentafluorothiophenol (PFTP) layer. The figure compares the stretched exponential dependence of the threshold voltage shift for two identically fabricated transistors, one with a coated dielectric and the other with a bare dielectric. Fitting parameters are shown in the inset. The relaxation time τ is a direct measure of the operational stability. Highlights: All-inkjet printed OTFTs with a field effect mobility of 0.1 cm 2 /(V s) were fabricated and characterized. Ink-jet printed pentafluorothiophenol neutralize defects on the dielectric surface. The properties of the solvents used in the ink formulations have a crucial role on the OTFT environmental stability. Abstract: We report about the use of a printed pentafluorothiophenol layer on top of the dielectric surface as a passivation coating to improve the operational stability of all-ink-jet printed transistors. Transistors with bottom-gate structure were fabricated using cross-linked poly-4-vinylphenol (c-PVP) as dielectric layer and an ink formulation of an amorphous triarylamine polymer as semiconductor. The resulting TFTs had low turn-on voltage ( Vth  < |5 V|) and a mobility ≈0.1 cm 2 /(V s). A comparison of identically fabricated transistors shows that devices with coated dielectric have a higher operational stability than those using bare c-PVP. This conclusion is supported by a quantitative study of the threshold voltage shift with time under continuous operation. Long exposure to the ambient atmosphere causes an increase in the threshold voltage strongly dependent on the used semiconducting ink formulation.